(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the current situation of cesarean section according to Robson classification, maternal and fetal complications due to cesarean section at Thanh Nhan Hospital. Methods: This retrospective study was conducted on caesarean section records at Thanh Nhan Hospital from January 1, 2019, to December 31, 2019. The study sample included records with complete information on caesarean section, with gestational age > 22 weeks and weight > 500 grams. Results: In 2019, there were 2539 deliveries at Thanh Nhan Hospital, of which 1352 were caesarean section, accounting for 53.2%. Robson classification, groups 6, 7, 8, and 9 had an absolute caesarean section rate (100%); group 5 had a rate of 99.8%; and group 3 had the lowest rate (18.6%). Complications due to anesthesia accounted for 1.6%; superficial wound infections accounted for 1.6%; and postoperative bleeding accounted for 0.7%. Neonatal jaundice accounted for 4.5%; neonatal infections accounted for 1.8%; and Apgar score < 7 at 5 minutes accounted for 0.9%. Conclusion: The caesarean section rate at Thanh Nhan Hospital in 2019 was 53.2%. Maternal and neonatal complications due to caesarean section need to be better managed to minimize risks.